Application in Qualitative & Quantitative Research - Abdillah, Abdillah; Widianingsih, Ida; Buchari, Rd Ahmad; Nurasa, Heru (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2025)
The aim of this study is to explain the discourse and differences between research, quantitative research and qualitative research. Qualitative research, based on the philosophy of postpositivism, is used to examine the condition of natural objects with the aim of understanding phenomena. Qualitative research is an intense communication process between the researcher and the phenomenon being studied. Quantitative research, which is based on the philosophy of positivism, is used to study a specific population or sample, collect data using research instruments, and then analyze the data quantitatively or statistically to test a predetermined hypothesis. Quantitative research and qualitative research differ in terms of the criteria, processes, and competencies used.